Silk fibroin nanofibers: a promising ink additive for extrusion three-dimensional bioprinting. (September 2020) - Sakai, S.; Yoshii, A.; Sakurai, S.; Horii, K.; Nagasuna, O.
Abstract: Here, we investigated the usefulness of silk fibroin nanofibers obtained via mechanical grinding of degummed silkworm silk fibers as an additive in bioinks for extrusion three-dimensional (3D) bioprinting of cell-laden constructs. The nanofibers could be sterilized by autoclaving, and addition of the nanofibers improved the shear thinning of polymeric aqueous solutions, independent of electric charge and the content of cross-linkable moieties in the polymers. The addition of nanofibers to bioinks resulted in the fabrication of hydrogel constructs with higher fidelity to blueprints. Mammalian cells in the constructs showed >85% viability independent of the presence of nanofibers. The nanofibers did not affect the morphologies of enclosed cells. These results demonstrate the great potential of silk fibroin nanofibers obtained via mechanical grinding of degummed silkworm silk fibers as an additive in bioinks for extrusion 3D bioprinting. Graphical abstract: Image 1 Highlights: Silk fibroin nanofibers are sterilizable by autoclaving. Shear thinning of polymer solutions was enhanced by silk fibroin nanofibers. Inks containing silk fibroin nanofibers realize bioprinting with high printability. Silk fibroin nanofibers in bioinks are cytocompatible. Silk fibroin nanofibers are inert toward cells in bioprinted hydrogels.